A Revolution Of Human Resources In Era Of Industry 4.0 - Sri Rahayu; Rieka Ramdhaniyah (Proceeding International Conference on Information Technology and Business, 2019)
This research will explain about a rovlution of human resources in the industrial era 4.0. Human resources needed by the industry today who have competence in digital technology. People must have expertise and experience especially technology development to follow era industril revolution 4.0. For this reason, an increase in skills (up-skilling) or expertise (reskilling) for human resources is based on the needs of the industrial world. This study uses a qualitative participatory research method, which emphasizes research results in the researcher is directly involved as a research instrument. Data obtained through literature studies and interviews. The results of this study will explain human resources in the industrial revolution era 4.0. competent human resources.Keywords: Human Resouces, Comptencies, Skill, Revolution 4.0